Mosquito community structure in phytotelmata from a South American temperate wetland - Albicócco, A.P. (2011)
Phytotelmata, or plant-held waters, are considered to be good model systems for the study of community ecology. The fauna of these natural container habitats, particularly the mosquitoes, have been extensively investigated in tropical regions, but there is little known about them in temperate South America. We assessed the structure of immature mosquito communities in leaf axils, tree holes, and bamboo stumps from a temperate wetland of Argentina. A total of 4,330 immature mosquitoes were collected among the 2,606 phytotelmata inspected. Leaf axils of eight plant species and tree holes were larval habitats for nine mosquito species belonging to the genus Culex, Wyeomyia, Isostomyia, and Toxorhynchites. The mosquito communities showed richness ranging from one to four species. Marked differences were detected in the plant specificity for the species collected. Some of them were exclusively found in one plant species (Isostomyia paranensis in Scirpus giganteus), whereas others were collected in up to five plant species but belonging to the same phytotelm class, the leaf axils. Those from tree holes are well-known dwellers of artificial containers and ground water habitats, such as Culex pipiens. Our results support the idea of low mosquito richness in phytotelmata from temperate regions in comparison with tropical areas, but the observed specificity patterns echo the findings of tropical forests. © 2011 The Society for Vector Ecology.